Facilities Availability to Support Teaching and Learning Process and Public Reactions Toward Technical Education - Raheef , Oparinde Olayiwola (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study adopted a descriptive survey research design. The population for this study comprised members of the top management team, all teachers, non-teaching staff, and students (hereby referred to as stakeholders) in the 12 technical schools across the three federal constituencies in Osun State. We used a multi-stage sampling procedure to group the schools in the three senatorial districts of Osun State. For the study, we purposefully selected one local government area (LGA) with a technical college from each state senatorial district. We selected one technical college in each LGA for the study using a simple random sampling technique. We used the total enumeration sampling technique in each school to select all the top management teams, resulting in a total of 15 teams, each consisting of five members. We also used the convenience sampling technique to select 150 stakeholders from technical schools, with each senatorial district hosting 50 participants. The study employed two self-designed research instruments, the Facilities Availability Questionnaire (FA-Q) and the Stakeholders’ Perception Questionnaire (SP-Q). We used the mean and standard deviation of descriptive statistics for data analysis. Findings from the study revealed that there were facilities available to support teaching and learning processes in technical schools in Osun State; however, facilities such as internet access and functioning air conditioning were not available. The study concluded that the availability of facilities to support the teaching and learning process is essential for the effective delivery of technical education in Osun State.